The Host CYP1A1-Microbiota Metabolic Axis Promotes Gut Barrier Disruption in Methicillin-Resistant Staphylococcus aureus-Induced Abdominal Sepsis - Ma, Xiaoyuan; Jin, Huaijian; Chu, Xiang; Dai, Weihong; Tang, Wanqi; Zhu, Junyu; Wang, Fangjie; Yang, Xue; Li, Wei; Liu, Guodong; Yang, Xia; Liang, Huaping (Frontiers in Microbiology, 2022)
Background: Host-microbiota crosstalk has been implicated in multiple host metabolic pathway axes regulating intestinal barrier function. While constitutive CYP1A1 expression perturbs the microbiome-derived autoregulatory loop upon enteric infection, little is known about the role of host CYP1A1 in modulating gut microbiome-mediated signalling during methicillin-resistant Staphylococcus aureus (MRSA)-induced abdominal sepsis and its effects on intestinal barrier integrity. Methods: Abdominal sepsis was induced by intraperitoneal injection of MRSA in mice. The effect of CYP1A1 deficiency on gut barrier integrity was investigated using RNA sequencing, microbiome analyses, and targeted metabolomics. The microbiota-produced metabolites were validated in sepsis patients with persistent MRSA infection. Results: Mice lacking CYP1A1 exhibited an altered gut microbiome, a reduction in the metabolic shift from lysine to cadaverine in cecal contents, and antimicrobial molecule production (Retnlb, Gbp7, and Gbp3), and they were protected against gut barrier disruption when subjected to MRSA challenge. These beneficial effects were validated in AHR knockout (KO) mice by cohousing with CYP1A1 KO mice and could be abrogated after supplementation with cadaverine or E. faecalis, the primary microbiota genus for cadaverine synthesis. Antibiotics-driven gut dysbacteriosis impaired the survival benefit and disrupted intestinal barrier integrity in CYP1A1 KO mice after MRSA infection. Furthermore, increased cadaverine levels in faeces and serum were detected in critically ill patients with gut leakiness during persistent MRSA infection, whereas cadaverine was not detected in healthy controls. In addition, microbiota-derived cadaverine induced enterocyte junction disruption by activating the HRH4/NF-κB/MLCK signalling pathway. Conclusion: This study reveals the unexpected function of host CYP1A1 in microbiota-mediated cadaverine metabolism, which has important consequences for dysbacteriosis upon MRSA-induced abdominal sepsis, indicating that inhibiting CYP1A1 or blocking cadaverine-HRH4 signalling could be a potential therapeutic target against abdominal sepsis.